2019
DOI: 10.1016/j.cognition.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

It takes me back: The mnemonic time-travel effect

Abstract: Given the links between motion and temporal thinking, it is surprising that no studies have examined the possibility that transporting participants back mentally towards the time of encoding could improve memory. Six experiments investigated whether backward motion would promote recall relative to forward motion or no-motion conditions. Participants saw a video of a staged crime (Experiments 1, 3 and 5), a word list (Experiments 2 and 4) or a set of pictures (Experiment 6). Then, they walked forward or backwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Many studies have explored the relationship between decompensated cardiac remodelling and cardiac substrate utilization. Whereas the question of whether FFA utilization is decreased [6467] or unchanged [68, 69] during compensated hypertrophy remains subject to debate, the majority of studies reported that the development of overt cardiac dysfunction is accompanied by reduced FFA oxidation [70, 71] (Figure 2A) . This metabolic shift was confirmed in multiple animal models of HF, including ischaemic [72] and pacing-induced [73] HF, and was supported by clinical studies reporting a reduced FFA oxidative capacity in HF [74, 75].…”
Section: Myocardial Metabolic Adaption To Stressmentioning
confidence: 99%
“…Many studies have explored the relationship between decompensated cardiac remodelling and cardiac substrate utilization. Whereas the question of whether FFA utilization is decreased [6467] or unchanged [68, 69] during compensated hypertrophy remains subject to debate, the majority of studies reported that the development of overt cardiac dysfunction is accompanied by reduced FFA oxidation [70, 71] (Figure 2A) . This metabolic shift was confirmed in multiple animal models of HF, including ischaemic [72] and pacing-induced [73] HF, and was supported by clinical studies reporting a reduced FFA oxidative capacity in HF [74, 75].…”
Section: Myocardial Metabolic Adaption To Stressmentioning
confidence: 99%
“…To allow the experiment to be run on the same computer without interruption, the word list, the Tetris game, the video clip, and the memory test were all presented within the same computer program written in LiveCode (see https://livecode.com). Aksentijevic et al (2019) report measures of 26.7 cm  19.9 cm for the video used for the optic-flow manipulation (resulting in visual angles of 33.05°Â 25°at a viewing distance of 45 cm). This corresponds to a 4:3 aspect ratio and thus differs from the 16:9 aspect ratio of the original 1,280  720 pixel train journey video.…”
Section: Differences To the Original Studymentioning
confidence: 99%
“…The significance level is set to .05. The most critical of the comparisons reported by Aksentijevic et al (2019) is that between the backward condition and the forward condition. Based on the test statistics reported by Aksentijevic et al, a sample effect size of d z = 1.05 for the within-subject comparison between these conditions can be assumed.…”
Section: Analysis Plan Hypothesis and Power Analysismentioning
confidence: 99%
See 2 more Smart Citations